2022
DOI: 10.2196/30974
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Lifestyle Interventions for Survivors of Cancer: Usability Study

Abstract: Background Internet-based lifestyle programs are increasingly being used to deliver health behavior change interventions to survivors of cancer. However, little is known about website use in this population or its association with healthy lifestyle changes. Objective The aim of this study is to describe lifestyle intervention website use (log-ins, time on website, and page views) among survivors of cancer and patterns of use by participant characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Ultimately, 9 studies (31-39) met the inclusion criteria of our review and were subjected to data extraction. (32), Nutrition and Cancer (33), JMIR mHealth and uHealth (34), Journal of Medical Internet Research (35), Journal of the Academy of Nutrition and Dietetics (36), Nutrition (37), JMIR Formative Research (38) and Nutrients (39). All records were written in English.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately, 9 studies (31-39) met the inclusion criteria of our review and were subjected to data extraction. (32), Nutrition and Cancer (33), JMIR mHealth and uHealth (34), Journal of Medical Internet Research (35), Journal of the Academy of Nutrition and Dietetics (36), Nutrition (37), JMIR Formative Research (38) and Nutrients (39). All records were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al (38) conducted a single-arm pilot study of the Survivor SHINE lifestyle intervention website and found that increased use of the website correlated with improvements in physical activity. However, there was no association between the frequency of logins or total time on the website and improvements in healthy lifestyle knowledge or changes in body weight or food intake among survivors of cancers with >80% 5-year survival (e.g., breast, prostate, and thyroid cancers).…”
Section: The Effects Of Web-based Nutrition In Adult Cancer Survivorsmentioning
confidence: 99%
See 2 more Smart Citations